Aggression, Social Stress, and the Immune System in Humans and Animal Models - Takahashi, Aki; Flanigan, Meghan E.; McEwen, Bruce S.; Russo, Scott J. (Frontiers in Behavioral Neuroscience, 2018)
Social stress can lead to the development of psychological problems ranging from exaggerated anxiety and depression to antisocial and violence-related behaviors. Increasing evidence suggests that the immune system is involved in responses to social stress in adulthood. For example, human studies show that individuals with high aggression traits display heightened inflammatory cytokine levels and dysregulated immune responses such as slower wound healing. Similar findings have been observed in patients with depression, and comorbidity of depression and aggression was correlated with stronger immune dysregulation. Therefore, dysregulation of the immune system may be one of the mediators of social stress that produces aggression and/or depression. Similar to humans, aggressive animals also show increased levels of several proinflammatory cytokines, however, unlike humans these animals are more protected from infectious organisms and have faster wound healing than animals with low aggression. On the other hand, subordinate animals that receive repeated social defeat stress have been shown to develop escalated and dysregulated immune responses such as glucocorticoid insensitivity in monocytes. In this review we synthesize the current evidence in humans, non-human primates, and rodents to show a role for the immune system in responses to social stress leading to psychiatric problems such as aggression or depression. We argue that while depression and aggression represent two fundamentally different behavioral and physiological responses to social stress, it is possible that some overlapped, as well as distinct, pattern of immune signaling may underlie both of them. We also argue the necessity of studying animal models of maladaptive aggression induced by social stress (i.e. social isolation) for understanding neuro-immune mechanism of aggression, which may be relevant to human aggression.